Evaluasi User Experience Pada Game Hearthstone Dengan Menggunakan Metode Game Experience Questionnaire - Naufal Rizky Akbar; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Hearthstone is a digital Collectible Card Game that's pretty successful, this is proven by its achievement as a Card Game eSport with a lot of fans. But, unfortunately Hearthstone still has several flaw, one of its major flaw is the high difficulty experienced by the new player. Looking at that problem, Evaluation to the game's user experience needs to be done. Currently, there's a lot of method that could be used to evaluate user experience of a software. But, a lot of those method often isn't designed to specifically evaluate user experience of a game. That's why, the evaluation method that's used in this research is an evaluation method that's specifically designed to be used to evaluate user experience of a game, which is Game Experience Questionnaire. Based on the evaluation result, Hearthstone scored the lowest at Immersion and Returning to Reality aspect that could be improved by imitating the story part of its competitor, which is Shadowverse.